2021
DOI: 10.1519/jpt.0000000000000301
|View full text |Cite
|
Sign up to set email alerts
|

Mobility Limitation in Older Adults Residing in Nursing Homes in Brazil Associated With Advanced Age and Poor Nutritional Status: An Observational Study

Abstract: Background and Purpose: Mobility is a basic human need, and its limitation compromises health status, especially in older adults from developing countries and residing in nursing homes. This study aims to determine the prevalence and factors associated with mobility limitation in older adults residing in nursing homes. Methods: A cross-sectional study was conducted with 305 older adults (≥60 years) residing in 10 nursing homes in Northeast Brazil. Mobility limitation was evaluated using the “walking” item of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
(132 reference statements)
0
4
0
Order By: Relevance
“…Mobility limitations have a high prevalence among older adults living in residential homes [ 13 ]. Despite the benefits of exercise programs for people with and without reduced mobility, older people living in residential homes tend to higher prevalence of physical inactivity and lower levels of participation in the centers' exercise programs [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mobility limitations have a high prevalence among older adults living in residential homes [ 13 ]. Despite the benefits of exercise programs for people with and without reduced mobility, older people living in residential homes tend to higher prevalence of physical inactivity and lower levels of participation in the centers' exercise programs [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pereira et al confirmed our findings, identifying that two out of three institutionalized older adults had malnutrition and sarcopenia [ 35 ]. Malnutrition leads to lower muscle strength and less physical activity [ 36 ], which is reflected in this study by the low scores in the hand-grip muscle strength and in the Gait Speed, and reinforced by the high % time in SB [ 36 ], which also was identified as an associated factor with sarcopenia.…”
Section: Discussionmentioning
confidence: 93%
“…Two studies report that that higher levels of SB were found to be associated with higher levels of sarcopenia [ 36 , 37 ]. Physical inactivity contributes to development of sarcopenia, whether due to disease-related immobility or disability, or to a sedentary lifestyle, which has been shown to be a risk factor for muscle weakness that in turn, results in reduced activity levels, loss of muscle mass, and muscle strength [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in relation to SB, two studies report that higher levels of SB are associated with higher levels of sarcopenia [11,12]. Physical inactivity contributes to the development of sarcopenia, either due to disease-related immobility or disability, or to a sedentary lifestyle, which has been shown to be a risk factor for muscle weakness [13].…”
Section: Sb In the Population Of Older Adultsmentioning
confidence: 99%